Rapid detection of GES-type extended-spectrum β-lactamases in Pseudomonas aeruginosa with a peptide nucleic acid-based realtime PCR assay - Ehlers, M.M. (Marthie Magdaleen) (University of Pretoria, 2013)
Dissertation (MSc (Medical Microbiology))--University of Pretoria, 2008.